EMPIRICAL DIRECTIONS TO DESIGNING SUSTAINABLE IN-SERVICE TRAINING FRAMEWORK FOR PRIMARY SCHOOL TEACHER IN CAMBODIA - Phin, Chankea (PUPIL: International Journal of Teaching, Education and Learning, 2017)
In-service training is an imperative for ongoing flexible development of teacher in this changing world. This study is to explore directions to ensure this need that later the study will propose a design of these exemplary sustainable in-service training frameworks. The study administered questionnaire surveys, interviews, and school visits in total of seven stages of field studies in Cambodia, in addition to existing literatures. As such, quantitative and qualitative analyses were made carefully. The results of the study found that (1) teachers acknowledged the significance of in-service training opportunity for their personal/professional/school development, (2) they desire to have regular opportunities in their career, (3) they need an actionable framework for it; but (4) they face some challenges within their schools specifically schools in rural and remote areas. The study would suggest: a) extend to larger survey samples, b) test the designed framework to see how effective and efficient it will be and to what extent it will get sustainable, and c) further find ways to raise awareness from more teachers to make more acceptable decision in their career, from community people to support teacher education, and from stakeholders to provide timely supports to teachers especially rural and remote teachers.